Changes in size and trophic structure of the nanoflagellate assemblage in response to a spring phytoplankton bloom in the central Yellow Sea - Lin, Shiquan; Huang, Lingfeng; Zhu, Zhisheng; Jia, Xiaoyan; 黄凌风 (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
National Basic Research Program of China [2006CB400604, 2011CB409804]; National Natural Science Foundation of China [40876078] On a multidisciplinary investigation cruise from March 25 to April 14, 2009, the dynamics of the nanoflagellate (NF) assemblage in response to a spring phytoplankton bloom was observed in the central Yellow Sea (similar to 33.5-37 degrees N, similar to 120.5-124.5 degrees E). The water mass of the bloom was followed with a drifting buoy-guided Lagrangian tracing approach. The results showed that the abundance, biomass, cell size composition and trophic structure of NFs dramatically changed with the succession of the bloom. Compared with that in the Pre-bloom phase, the cell abundance and biomass of NFs increased more than two-fold in the Bloom phase and the Post-bloom phase in the water column, respectively, especially in the deep chlorophyll maximum (DCM) layer. NF cell abundance was composed mainly of 2-5 mu m pigmented photosynthetic nanoflagellates (PNFs), whose rapid growth in response to the bloom outbreak characterized the NF dynamics in the bloom phase. Although larger (5-20 mu m) flagellates constituted less than 20% of NF cell abundance in most samples, they accounted for a rather larger percentage in NF biomass, especially in the bloom decline phase, when the response of the NF assemblage to the spring bloom was characterized by a dramatic increase in NF biomass, mainly contributed by 10-20 mu m PNFs and non-pigmented heterotrophic nanoflagellates (HNFs). Compared to PNFs, HNFs showed a rather mild response during the bloom, especially in the 2-5 mu m fraction, which decreased during the bloom, despite a significant increase of both HNFs and PNFs in the early stage of the bloom. However, when PNFs were declining in the Post-bloom phase, HNFs, especially the 5-10 mu m fraction, had in contrast shown an ascending trend. This is the first systematic report on short-term dynamics of different nano-sized flagellate components, and our results suggested an inherent mechanism associated with cell size as well as trophic strategies for the dynamics of the NF assemblage in response to the spring phytoplankton bloom, within which mixotrophy in PNFs might play a substantially important role. (C) 2013 Elsevier Ltd. All rights reserved.